Local day-care quality and maternal employment: Evidence from East and West Germany - Pia S. Schober; C. Katharina Spieß (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
By investigating how locally available early childhood education and care quality relates to maternal employment choices, this study extended the literature which has mostly focused on the importance of day-care availability or costs. We provided differentiated analyses by the youngest child's age and for West and East Germany to examine moderating influences of varying day-care supply and work-care cultures. The empirical analysis linked the Socio-Economic Panel and the 'Families in Germany'-Study for 2010 and 2011 (N=3,301 mothers) with regional structural quality data. We used regression models of employment status and work hours changes, respectively. In East Germany, mothers with a child aged under three years who lived in districts with smaller day-care groups were more likely to be employed and to extend their work hours. In West Germany, the negative association of child-teacher-ratios with maternal employment was marginally significant. For mothers with older children, day-care quality was unrelated to employment.
Keywords: 330; child care; child care arrangements; education; early childhood; family policy; maternal employment